2014
DOI: 10.1371/journal.pone.0090704
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 in Lipid Rafts Interacts with Dengue Virus NS3 during Polyprotein Processing and Replication in HMEC-1 Cells

Abstract: Lipid rafts are ordered microdomains within cellular membranes that are rich in cholesterol and sphingolipids. Caveolin (Cav-1) and flotillin (Flt-1) are markers of lipid rafts, which serve as an organizing center for biological phenomena and cellular signaling. Lipid rafts involvement in dengue virus (DENV) processing, replication, and assembly remains poorly characterized. Here, we investigated the role of lipid rafts after DENV endocytosis in human microvascular endothelial cells (HMEC-1). The non-structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Enrichment in SLs and a reduction of PC levels are characteristics of liquid ordered membrane microdomains or membrane rafts (7,9,18,56). Since membrane raft-like microdomains, including those located in the ER (57), are usually cholesterol enriched (7,9,18,56), our findings could be connected to the role(s) of membrane microdomains enriched in cholesterol in flavivirus infections (28,31,(58)(59)(60). SL-enriched membrane microdomains have functional properties directly linked to their lipid composition, such as coalescence and the promotion of budding processes during virus assembly (7,9) or exosome biogenesis (18).…”
Section: Discussionmentioning
confidence: 57%
“…Enrichment in SLs and a reduction of PC levels are characteristics of liquid ordered membrane microdomains or membrane rafts (7,9,18,56). Since membrane raft-like microdomains, including those located in the ER (57), are usually cholesterol enriched (7,9,18,56), our findings could be connected to the role(s) of membrane microdomains enriched in cholesterol in flavivirus infections (28,31,(58)(59)(60). SL-enriched membrane microdomains have functional properties directly linked to their lipid composition, such as coalescence and the promotion of budding processes during virus assembly (7,9) or exosome biogenesis (18).…”
Section: Discussionmentioning
confidence: 57%
“…The knockout was performed according to the protocol (37). lentiCRISPR v2 was a gift from Feng Zhang (Addgene plasmid # 52961; http://n2t.net/addgene:52961; RRID:Addgene_52961 • C for 45 s and more tubes were placed on ice for 2 min.…”
Section: Knockout Of Asc By Crispr-cas9 Technologymentioning
confidence: 99%
“…These characteristics include the hydrophilic segment, which is required for the cofactor activity of viral protease NS3, and the 3 hydrophobic regions that are thought to be responsible for membrane association and to generate the MDA. In addition, we previously demonstrated that NS2B is localized in cellular membranes (particularly in lipid rafts) due to the hydrophobic regions [ 20 ]. Data from a subsequent study suggested that the NS2B protein contains alpha-helical transmembrane domains that direct folds within micelles, indicating the ability of this protein to associate with membranes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%